2008
DOI: 10.1227/01.neu.0000311075.56486.c5
|View full text |Cite
|
Sign up to set email alerts
|

Standard Open Microdiscectomy Versus Minimal Access Trocar Microdiscectomy

Abstract: SOMD and MAMD allow achievement of significant improvement of pain and neurological deficits in patients with lumbar disc herniations. Differences in operative time, blood loss, and complication rates were statistically not significant in MAMD compared with SOMD, indicating that, at least in lumbar disc surgery, minimal access trocar techniques are a viable alternative to standard spinal approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
2
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(99 citation statements)
references
References 30 publications
7
88
2
2
Order By: Relevance
“…A total of 1886 titles and abstracts were preliminarily reviewed, of which 11 studies [11][12][13][14][15][16][17][18][19][20][21] eventually satisfied the eligibility criteria (Fig. 1).…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 1886 titles and abstracts were preliminarily reviewed, of which 11 studies [11][12][13][14][15][16][17][18][19][20][21] eventually satisfied the eligibility criteria (Fig. 1).…”
Section: Search Resultsmentioning
confidence: 99%
“…4). Longterm VAS scores were available in 3 of the studies [11,17,21]. The study found no significant differences between the ILMI and MD groups (SMD = 0.13, 95% CI −0.04, 0.30; p = 0.14) (Fig.…”
Section: Back Painmentioning
confidence: 98%
See 2 more Smart Citations
“…Huang et al [15] reported increased C-reactive protein and interleukin-6 serum levels in open discectomies, and Arts et al [4] demonstrated that within-patient relative change in CPK is lower in minimally invasive spine approaches, but failed to show any difference between MED and MSD in terms of multifidus muscle atrophy [1]. With respect to clinical results, randomised trials comparing tubular microdiscectomy or microendoscopic discectomy with conventional microdiscectomy failed to demonstrate the superiority of tubular techniques in early or long-term outcomes [2,3,12,20,30,32,33].…”
Section: Discussionmentioning
confidence: 99%